2020
DOI: 10.1002/acm2.13048
|View full text |Cite
|
Sign up to set email alerts
|

Quantified VMAT plan complexity in relation to measurement‐based quality assurance results

Abstract: Volumetric‐modulated arc therapy (VMAT) treatment plans that are highly modulated or complex may result in disagreements between the planned dose distribution and the measured dose distribution. This study investigated established VMAT complexity metrics as a means of predicting phantom‐based measurement results for 93 treatments delivered on a TrueBeam linac, and 91 treatments delivered on two TrueBeam STx linacs. Complexity metrics investigated showed weak correlations to gamma passing rate, with the excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…For example, treatment plans for the head and neck (H&N) are generally more complex than for the prostate 50 . The complexity of the treatment plan affects the accuracy of dose delivery, and a complex treatment plan increases failing points and decreases GPR 51–54 . It could also affect the accuracy of the gamma distribution synthesis and the GPR prediction of the GAN model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, treatment plans for the head and neck (H&N) are generally more complex than for the prostate 50 . The complexity of the treatment plan affects the accuracy of dose delivery, and a complex treatment plan increases failing points and decreases GPR 51–54 . It could also affect the accuracy of the gamma distribution synthesis and the GPR prediction of the GAN model.…”
Section: Discussionmentioning
confidence: 99%
“…50 The complexity of the treatment plan affects the accuracy of dose delivery, and a complex treatment plan increases failing points and decreases GPR. [51][52][53][54] It could also affect the accuracy of the gamma distribution synthesis and the GPR prediction of the GAN model. Our study showed that the sensitivity of failing points was increased with tighter tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For STD, the MCSv has a value around 0.172. The values in SW are among the lowest compared to those found in the literature 23,26–28 . While specific results may not be applied to other institutions, the results can be used to develop institute specific QA tools to aid in the treatment planning process.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, 800 MUs seems to be a good compromise between a dosimetric plan of the same quality as the SO‐STD referential plan, a satisfactory pre‐treatment measurement and a modulation controlled by the MLC complexity metrics. Previous studies 23,26 of complexity metric correlations generally report weak to moderate correlations to QA results. For this study, the complexity metrics selected were used to describe the general MLC movement and aperture shape of treatments, not to determine a correlation with the pre‐processing QA.…”
Section: Discussionmentioning
confidence: 92%
“…When developing standard plan protocols or class solutions, it is common practice to limit certain features within the planning system that might increase the plan complexity, which could result in low PSQA pass rates. 16,17 Figure 2 shows the frequency of plan features that the participating centers indicated were limited for IMRT and VMAT based on the impact that these have on the PSQA pass rates (Supporting Information, A4, A5). The most common limiting features reported were minimum segment size for IMRT and dose computation (spatial) resolution for VMAT.…”
Section: A | Policy and Proceduresmentioning
confidence: 99%